Development Strategy of Communication on Cardiovascular Disease Prevention for Risk Group - Chivachaichawan, Punnapat; Saengthong, Suchat; Vongkamjan, Supawan (Mediterranean Journal of Social Sciences, 2012)
The research objectives were 1) to construct development strategy of communication on cardiovascular disease prevention for risk group in Chainat Municipality, 2) to experiment the constructed development strategy of communication on cardiovascular disease prevention for risk group in Chainat Municipality, and 3) to determine satisfaction level of experiment group for implementation development strategy of communication on cardiovascular disease prevention for risk group in Chainat Municipality. The research design was mixed methods of quantitative and qualitative approaches. The purposive sampling was used for sampling 310 community peoples of risk group in Chainat Municipality, Chainat Province on perception on. The qualitative research with focus group discussion and in-depth Interview were conduct with stakeholders from risk group in Chainat Municipality, community leaders, health volunteer and experts from Jainad Narendra Hospital included professional nurses of Department of Medicine, public health personnel, nutritionists, physicians, risk group and handlers. The purposive sampling was employed for selection of 53 community people from risk group for Quasi-experimental research. The results were as followings: the constructed economic status elevation based on SEP comprised 3 system units included 1) Risk Assessment, 2) Risk Management and 3) Monitoring the Results. The mean scores of posttest in aspects of risk opportunity, severity of cardiovascular disease, and self-health toward cardiovascular disease were higher than pretest at statistically significant level of 0.01, 0.01, and 0.01. Their whole satisfaction level was at very good level for risk communication model, content, media and equipments to raise awareness.